Large‐scale experimental observations of sheet flow on a sandbar under skewed‐asymmetric waves. Issue 6 (22nd June 2017) - Mieras, Ryan S.; Puleo, Jack A.; Anderson, Dylan; Cox, Daniel T.; Hsu, Tian‐Jian
Abstract: A novel large wave flume experiment was conducted on a fixed, barred beach with a sediment pit on the sandbar, allowing for the isolation of small‐scale bed response to large‐scale forcing. Concurrent measurements of instantaneous sheet layer sediment concentration profiles and near‐bed velocity profiles were obtained on a sandbar for the first time. Two sediment distributions were used with median grain diameters, d 50, of 0.17 and 0.27 mm. Sheet flow occurred primarily under wave crests, where sheet thickness increased with increasing wave height. A proportionality constant, Λ, was used to relate maximum Shields parameter to maximum sheet thickness (normalized by d 50 ), with bed shear stress computed using the quadratic drag law. An enhanced sheet layer thickness was apparent for the smaller sediment experiments ( Λ = 18.7), when directly compared to closed‐conduit oscillatory flow tunnel data ( Λ = 10.6). However, Λ varied significantly (5 < Λ < 31) depending on the procedure used to estimate grain roughness, k s, and wave friction factor, f w . Three models for k s were compared (keeping the model for f w fixed): constant k s = 2.5 d 50, and two expressions dependent on flow intensity, derived from steady and oscillatory sheet flow experiments. Values of k s / d 50 varied by two orders of magnitude and exhibited an inverse relationship with Λ, where Λ ∼ 30 for k s / d 50 of O (1) while Λ ∼ 5 for k s / d 50 of O (100). Two expressions for f w were also tested (with the steady flow‐based model for k s ), yielding a difference of 69% ( Λ ∼ 13 versus Λ ∼ 22 ). Key Points: Instantaneous sheet flow concentration profiles and near‐bed velocities were measured concurrently on a sandbar for the first time Maximum dimensionless sheet thickness is larger under asymmetric surface waves than under currents in oscillatory flow tunnels Maximum Shields parameter is sensitive to the formulations for grain roughness and friction factor